ANALYSIS OF COAL DUST 63-53 MICROMETER CONCENTRATION EFFECT ON COAL DUST EXPLOSIBILITY USING 20 LITRE EXPLOSION CHAMBER - Basit, Abdul
Coal mining can be conducted using open-pit or underground methods. These mining activities must be carefully planned, especially regarding health and safety. Coal dust explosions are one of the potential threats that can occur in both open-pit and underground mines. This research aims to determine the explosibility of coal dust from Jambi Province using a 20-liter explosion chamber and a testing procedure following ASTM E1226 (2019). The tests were conducted using dust with a size of 63-53 ?m at concentrations of 600 g/m³, 800 g/m³, 1000 g/m³, 1100 g/m³, 1200 g/m³, 1400 g/m³, and 1600 g/m³, with a primary explosion initiated by a 5 kJ pyrotechnic ignitor. The results showed that increasing the dust concentration also increased the maximum pressure rise, but after a concentration of 1200 g/m³, the maximum pressure rise decreased due to the large number of coal dust particles that collide and agglomerate. From this research, the maximum pressure, maximum rate of pressure rise, and deflagration index were obtained as 10.05 bar, 411.01 bar/s, and 111.56 bar.m/s, respectively. Additionally, when compared to previous research, the size of the coal dust affects the maximum pressure, the more uniform and smaller the coal size, the greater the maximum pressure. Small dust will have a larger surface area so that it will burn more easily, and the uniformity of coal size makes the combustion process between dust more effective.